Folk Tales and Their Contemporary Reception - Cañadas García, Teresa (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2020)
The objective of this article is to analyze the folk tale concept and to make a review of the folk tales’ reception nowadays. I will take into account the changes of content and transmission criteria, thus focusing on the rewriting processes that folk tales have quite frequently undergone. Hence this article aims to illustrate pre-service school teachers with essential knowledge about folk tales and the variety of their current versions so that they can reflect on how to work with them in their future classrooms.